Implementation of Qur'an Reading and Writing Policy in Bekasi Schools: Supporting Factors, Challenges, and Strategies for Improvement - Amet Amet; Bambang Qamaruzzaman; Bambang Samsul Arifin; Qiqi Yuliati Zaqiah (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to analyze the implementation of policies to improve Quranic literacy (Baca Tulis Qur'an, BTQ) in schools/madrasahs, identify supporting and inhibiting factors, and provide strategic recommendations to improve the effectiveness of implementation. The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and policy document analysis. The research subjects included school/madrasah principals, BTQ teachers, and representatives of elementary and junior high school parents in Bekasi Regency. The results showed that the successful implementation of the BTQ policy was influenced by teacher competence, regional policy support, the availability of learning media, and parental participation. However, the main challenges included limited teacher training, a lack of innovation in learning methods, and infrastructure constraints. The conclusion of this study emphasizes the need for policy integration with adaptive learning strategies, teacher capacity building, and optimization of collaboration among stakeholders. These findings imply the need for local governments and educational units to develop sustainable BTQ teacher competency development programs and provide adequate resource support to strengthen the quality of BTQ learning.